A systematic review of implant outcomes in treated periodontitis patients. Issue 7 (18th September 2015) - Sousa, Vanessa; Mardas, Nikos; Farias, Bruna; Petrie, Aviva; Needleman, Ian; Spratt, David; Donos, Nikolaos
Abstract: Objectives: To investigate the effect of treated periodontitis on implant outcomes in partially edentulous individuals compared with periodontally healthy patients. Material and methods: Longitudinal studies reporting on implant survival, success, incidence of peri‐implantitis, bone loss and periodontal status, and on partially dentate patients with a history of treated periodontitis were included. Results: The search yielded 14, 917 citations. Twenty‐seven publications met the inclusion criteria for qualitative data synthesis. Implant success and survival were higher in periodontally healthy patients, whilst bone loss and incidence of peri‐implantitis was increased in patients with history of treated periodontitis. There was a higher tendency for implant loss and biological complications in patients previously presenting with severe forms of periodontitis. The strength of the evidence was limited by the heterogeneity of the included studies in terms of study design, population, therapy, unit of analysis, inconsistent definition of baselines and outcomes, as well as by the inadequate reporting of statistical analysis and accounting for confounding factors; thus, meta‐analysis could not be performed. Conclusions: Implants placed in patients treated for periodontal disease are associated with higher incidence of biological complications and lower success and survival rates than those placed in periodontally healthy patients. Severe forms of periodontal disease are associated with higher rates of implant loss. However, it is critical to develop well‐designed, long‐term prospective studies to provide further substantive evidence on the association of these outcomes.